Wounded Knee: A Moment of Cross-Racial Intersectionality or Cross-Racial Co-option? - Mansur Abdullah (The Toro Historical Review, 2025)
This paper aims to summarize the multiple narratives on the Wounded Knee standoff in 1973 between the American Indian Movement and the United States government, centering the paper on the relationship between American-Indian activists and Non-American-Indian activists. Trying to synthesize the narratives from Black, White, Latino(a), American Indian, and Asian activist sources and FBI documents to see how widespread and effective this popular front was at Wounded Knee. This was placed in the context of a wider debate over the role and importance of Non-American-Indian activists and whether they were trying to co-opt and whitewash the Wounded Knee standoff. What we see by comparing the sources is a grassroots movement of solidarity that was in collaboration with AIM’s leadership and goals.